The <u>like operato</u>r allows you to use pattern-matching characters to determine whether one string is equal to another string.
plz give me brainly
Answer:
f(-3)= -3
Step-by-step explanation:
We are given the function:
f(x) = 2x+3
and asked to find f(-3). Essentially, we want to find f(x) when x is equal to -3.
Therefore, we can substitute -3 for each x in the function.
f(x)= 2x+3 at x= -3
f(-3)= 2(-3) +3
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition and Subtraction
Multiply 2 and -3.
f(-3) = (2*-3) +3
f(-3)= (-6)+3
Add -6 and 3.
f(-3)= (-6+3)
f(-3)= -3
If f(x)= 2x+3, then<em> f(-3)= -3</em>
Answer:
t^6
Step-by-step explanation:
when dividing exponents, you subtract (refer to exponent rule)
t^12 - t^6 = t^6
Answer: Median Mode Mean
Step-by-step explanation:
A normal distribution a symmetric distribution where most of the values lies around the central peak where Mean, median mode all lies together and the value of z=0 (as z-value given the distance of data values from mean with respect to the standard deviation).
i.e. Z-score of 0 has 50% of the area to the left and 50% area to the right.
Hence, at a z-score of 0.0 in a normal distribution Mean, Median and Mode all fall together.
5^2 + 12^2 = c^2
25 + 144 = c^2
169 = c^2
take the square root of both sides
+ - 13 = c